A New Approach to Most Advanced Technique for Data Mining of the Big Data - pooja sharma; B.D. K. Patro (International Journal of Integrative Research, 2023)
Big data mining and analysis requires novel and improved techniques so that mixed types of data can be processed efficiently and effectively. Cluster, factor, regression, crowd-sourcing, and classification analysis are the main methods used in Big data. In the present research work, Big data storage, traditional data mining, Big data mining, Social recommendation, Scalable social recommendation and social recommendation improvement using deep learning are analyzed. The issues such as scalability, sparsity, cold start, data variety etc. are addressed by proposed approaches.